The relationship between family communication and Malay teenagers' perception of teenage pregnancy, sexuality and sex education - Farah Nabilah, Mohammad Anuar (2018)
Sexual problem among youths has become one of the major issues being debated amongst Malaysian society. The increasing number of teenagers who get pregnant before getting married is considered a disgrace by the Malaysian public. Previous studies have found that communication between children and their parents may affect teenagers’ perception of the idea of sexuality. Therefore, this study was conducted among teenagers in Alor Setar, Kedah to examine their perception of sexuality, teenage pregnancy and their family communication regarding sexuality. There were 132 Malay participants selected for this study, with ages ranging from 13 to 17 years old. Specifically, 82 participants were selected from students attending Sekolah Menengah Kebangsaan St Michael, and 50 participants from students living in an orphanage at Rumah Anak-Anak Yatim Darul Aitam Tunku Abdul Rahman (DATAR). Overall results show that majority of the participants had a conservativeinclined perception of sexuality as well as teenage pregnancy, and a moderate open communication with their family regarding sexuality. Further analysis reveals that the orphan participants presented with a more conservative perception of sexuality and teenage pregnancy when compared to the non-orphan participants. The overall result also shows that family communication does not have any significant relationship with perception of sexuality. However, daily school participants with parents who communicated more openly about sexuality issues will have a more conservative perception of sexuality and teenage pregnancy. In addition, girls were found to have a more conservative perception of both issues than boys. Discussion centres upon the importance of parental influence on promoting positive youth development, especially in obtaining appropriate sexual knowledge and reducing risky sexual behaviour among teenagers. The importance of sex education in school is also discussed.